2019
DOI: 10.14639/0392-100x-2165
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of hearing aid use in the elderly: the impact of age, cognition and hearing impairment

Abstract: Benefit of hearing aid use in the elderly: the impact of age, cognition and hearing impairment Il beneficio protesico e il ruolo delle abilità cognitive, dell'età e del deficit uditivo nel paziente anziano

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Elderly people often experience difficulty understanding speech, especially in demanding conditions, although there are large interindividual differences in speech recognition performance among older adults. Considered in isolation, age explains ~ 10–30% of variance in SRT in various tasks for groups of aided or unaided HI listeners (George et al, 2007 ; Van Esch and Dreschler, 2015 ; Bernstein et al, 2016 ; Lopez-Poveda et al, 2017 ; Tognola et al, 2019 ). This indicates that there is a link between age and speech recognition in noise, of lesser importance than the predictive effect of hearing loss mentioned earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly people often experience difficulty understanding speech, especially in demanding conditions, although there are large interindividual differences in speech recognition performance among older adults. Considered in isolation, age explains ~ 10–30% of variance in SRT in various tasks for groups of aided or unaided HI listeners (George et al, 2007 ; Van Esch and Dreschler, 2015 ; Bernstein et al, 2016 ; Lopez-Poveda et al, 2017 ; Tognola et al, 2019 ). This indicates that there is a link between age and speech recognition in noise, of lesser importance than the predictive effect of hearing loss mentioned earlier.…”
Section: Introductionmentioning
confidence: 99%
“…However, the degree of satisfaction with the hearing aids varies across the population of hearing aid users, which may lead to rare and irregular use of the devices (Lopez-Poveda et al 2017). This variation may be related to individual differences in cognitive abilities (Lunner, Rudner, and R€ onnberg 2009;Tognola et al 2019). In fact, previous research suggests that it is important to take into consideration, and understand the relationship between cognition and speech recognition in noise in individuals with hearing impairment, as cognitive factors may account for individual differences in the benefit obtained from hearing aid signal processing (Akeroyd 2008;Arehart et al 2013;Arehart et al 2015;Davies-Venn and Souza 2014;Desjardins 2016;Foo et al 2007;Lunner 2003;Ng et al 2013;Ohlenforst, Macdonald, and Souza 2015;Tognola et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This variation may be related to individual differences in cognitive abilities (Lunner, Rudner, and R€ onnberg 2009;Tognola et al 2019). In fact, previous research suggests that it is important to take into consideration, and understand the relationship between cognition and speech recognition in noise in individuals with hearing impairment, as cognitive factors may account for individual differences in the benefit obtained from hearing aid signal processing (Akeroyd 2008;Arehart et al 2013;Arehart et al 2015;Davies-Venn and Souza 2014;Desjardins 2016;Foo et al 2007;Lunner 2003;Ng et al 2013;Ohlenforst, Macdonald, and Souza 2015;Tognola et al 2019). However, evidence is mixed, as not all research studies support the relationship between hearing and cognition (Desjardins and Doherty 2014;F€ ullgrabe and Rosen 2016;Lopez-Poveda et al 2017;Neher et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, an additional advantage of the Smartphone + App set is the possibility of focusing the microphone and moving it closer to the sound source, thus improving the SNR when listening in noisy environments. Another advantage is the fact that mobile phones are widely distribuited, also in the elderly population, for whom several studies have found association between aided hearing outcomes and cognitive skills 12 .…”
Section: Discussionmentioning
confidence: 99%